STRESS AMONG PROSPECTIVE TEACHERS OF THE TEACHER EDUCATION INSTITUTIONS IN WEST BENGAL - Ray, Suvendu; Guha, Debjani (International Journal of Research -GRANTHAALAYAH, 2025)
Teaching is a stressful profession by nature, which has an impact on performance, job satisfaction, and general well-being. The stress levels of prospective teachers in West Bengal, an area with a dynamic and changing educational scene, are investigated in this study. Social expectations, job security worries, academic obligations, and difficult working conditions are just a few of the many stressors that prospective teachers must deal with. Their mental health may be severely impacted by these stressors, which may result in anxiety, burnout, and a reduction in their effectiveness as teachers. This purpose of the study was to investigate the stress levels experienced by prospective educators in West Bengal. So, a cross-sectional survey method has been used to conduct the study. A standardized mental stress scale was used in the study to collect data from 237 prospective teachers in West Bengal using a cross-sectional survey method. The scale offered a thorough assessment of stress levels and was divided into five subscales like Working Condition, Role Ambiguity and Conflict, Responsibility, Relationship, and Organizational Climate. Significant differences in stress levels by gender, location, academic stream, and institutional type were found when the data were analyzed using descriptive statistics and inferential tests. Results showed that trainees in the arts stream, government institutions, rural areas, and female teachers are more stressed than their peers. The study emphasized the need for targeted interventions to reduce stress among prospective teachers, including institutional support systems, stress management training, and personal well-being practices. These measures can enhance resilience, prepare educators better, and benefit the broader educational ecosystem. It has been found that proactive measures are crucial for navigating the professional journey and serve as a foundation for future research on stress management strategies in teacher education programmes.